2012
DOI: 10.1160/th12-04-0244
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of bleeding phenotype in adult patients with moderate or severe von Willebrand disease

Abstract: We performed a nation-wide cross-sectional study to evaluate determinants of bleeding symptoms in a large unselected cohort of adults with von Willebrand disease (VWD). VWD patients were included (n=664), based on lowest historically measured VWF:Ag and VWF:Act levels ≤30 U/dl. Menorrhagia (85%), cutaneous bleeding (77%), bleeding from minor wounds (77%) and oral-cavity bleeding (62%) occurred most frequently. Higher age was associated with a higher bleeding score (BS), determined according to Tosetto, in fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
175
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 92 publications
(185 citation statements)
references
References 41 publications
7
175
2
1
Order By: Relevance
“…Because VWF:Ag and FVIII:C levels are associated with bleeding phenotype in VWD, 14,16 it may be expected that VWFpp also associates with bleeding phenotype in VWD patients, either indirectly through its association with VWF:Ag or by binding to mature VWF in the circulation. 30 Interestingly, we found that the presence of VWFpp in patients with VWF:Ag levels ,5 IU/dL correlates with a milder bleeding phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because VWF:Ag and FVIII:C levels are associated with bleeding phenotype in VWD, 14,16 it may be expected that VWFpp also associates with bleeding phenotype in VWD patients, either indirectly through its association with VWF:Ag or by binding to mature VWF in the circulation. 30 Interestingly, we found that the presence of VWFpp in patients with VWF:Ag levels ,5 IU/dL correlates with a milder bleeding phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The inclusion criteria for the WiN study were hemorrhagic diathesis or a family history of VWD and historically low VWF levels #30 U/dL (VWF:Ag and/or VWF ristocetin cofactor [VWF:RCo]) and/or FVIII:C levels #40 U/dL. Patients were excluded if they were known to have other hemostatic disorders resulting in hemorrhagic diathesis.…”
Section: Methods Participantsmentioning
confidence: 99%
See 3 more Smart Citations